2021
DOI: 10.1186/s13071-021-05075-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mast cell stabilization on angiogenesis in primary and secondary experimental Trichinella spiralis infection

Abstract: Background Mast cells are known to affect the primary and secondary immune responses against parasites, and this effect is partially mediated through the release of pro-angiogenic mediators. The aim of this study was to explore the effect of the mast cell stabilizer (MCS), ketotifen, with and without albendazole, an anti-parasitic prescription medicine, on the inflammatory response against Trichinella spiralis, with the overall aim to investigate its effect on angiogenesis accompanying nurse ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Nurse cell formation exploits the metabolic machinery of the host and induces the formation of a vascular network to support its maintenance. Angiogenesis can be assessed by the estimation of microvascular density through tissue staining if certain endothelial cell markers such as CD31, in addition to the detection of inducers of inducers of angiogenesis such as VEGF ( El-Dardiry et al, 2021 ). In the current study, all drug regimens resulted in decreased CD31 immunohistochemical expression, and decreased gene expression of VEGF, as compared to the infected non-treated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurse cell formation exploits the metabolic machinery of the host and induces the formation of a vascular network to support its maintenance. Angiogenesis can be assessed by the estimation of microvascular density through tissue staining if certain endothelial cell markers such as CD31, in addition to the detection of inducers of inducers of angiogenesis such as VEGF ( El-Dardiry et al, 2021 ). In the current study, all drug regimens resulted in decreased CD31 immunohistochemical expression, and decreased gene expression of VEGF, as compared to the infected non-treated group.…”
Section: Discussionmentioning
confidence: 99%
“…They thus concluded that the expression of angiogenic factors such as thymosin β4 and VEGF serves to support the existence of nurse cells. ‘Infectious angiogenesis’ is a well-recognized concept in the pathogenesis of infectious diseases, and offers to be a promising therapeutic target to attenuate pathogen-induced pathology, in synergism with antimicrobial therapy ( Cerimele et al, 2003 ; El-Dardiry et al, 2021 ). Antiparasitic drugs that have an anti-angiogenic activity, in addition to their direct action on the parasite, merit special attention to be rediscovered and repurposed in the management of parasitic diseases ( Crump, 2017 ).…”
Section: Discussionmentioning
confidence: 99%